730. Hospital Readmissions Following Laboratory-Confirmed Influenza. (26th November 2018) - Dobrzynski, David; Ndi, Danielle; Markus, Tiffanie; Zhu, Yuwei; Schaffner, William; Talbot, H Keipp
Abstract: Background: Further understanding of hospital readmissions after influenza illness could reduce readmissions. The aim of our study was to characterize the morbidity associated with laboratory confirmed influenza hospitalizations. Methods: This was a retrospective study using data from 2006 to 2016 from the Tennessee (TN) Emerging Infections Program Influenza Surveillance Network, which prospectively identifies laboratory-confirmed influenza hospitalizations in Nashville, TN and surrounding counties. Using the TN Hospital Discharge Data System, which collects information on all hospitalizations and discharges in TN, cases were linked to subsequent hospitalizations up to 1 year. The International Classification of Diseases was used to define the primary diagnosis associated with each hospitalization. Demographic characteristics and outcomes were compared by using χ 2 tests for categorical variables. Multivariable logistic regression was used to compare study outcomes. Results: Of the 2, 897 patients with a laboratory-confirmed influenza hospitalization, 1, 364 (47%) had a hospital readmission during the subsequent year (figure). Multiple readmissions occurred in 740 patients (54%). The readmission group was older, female predominant, and had more comorbidities than patients not re-hospitalized. Acute COPD/asthma exacerbation, pneumonia, septicemia, and acute renal failure were the most common causes for readmission. Underlying cardiovascular disease (OR 1.6), lung disease (OR 1.6), kidney disease (OR 1.7), diabetes (OR 1.3), immunosuppression (OR 1.6), and liver disease (OR 2.1) were associated with increased risk of readmission (table). Conclusion: An influenza hospitalization is associated with increased hospital readmissions. Approximately 47% of patients hospitalized with influenza are readmitted within 1 year. Patient comorbidities could be an important link to influenza readmissions. Disclosures: W. Schaffner, Merck: Member, Data Safety Monitoring Board, Consulting fee. Pfizer: Member, Data Safety Monitoring Board, Consulting fee. Dynavax: Consultant, Consulting fee. Seqirus: Consultant, Consulting fee. SutroVax: Consultant, Consulting fee. Shionogi: Consultant, Consulting fee. H. K. Talbot, sanofi pasteur: Investigator, Research grant. Gilead: Investigator, Research grant. MedImmune: Investigator, Research grant. Vaxinnate: Safety Board, none. Seqirus: Safety Board, none.